2019
DOI: 10.1016/j.amjsurg.2018.12.018
|View full text |Cite
|
Sign up to set email alerts
|

Outcome after cholecystectomy in the elderly

Abstract: Take-down policy If you believe that this document breaches copyright please contact us providing details, and we will remove access to the work immediately and investigate your claim.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 27 publications
1
3
0
Order By: Relevance
“…The mortality in nonagenarians reported in another study was 5.5% and in another series of patients older than 70 years mortality was 6%, both of which are similar to the rate found by us in our study [ 19 , 20 ]. In another series, mortality rate in this age group reached 19.4% [ 21 ].…”
Section: Discussionsupporting
confidence: 91%
“…The mortality in nonagenarians reported in another study was 5.5% and in another series of patients older than 70 years mortality was 6%, both of which are similar to the rate found by us in our study [ 19 , 20 ]. In another series, mortality rate in this age group reached 19.4% [ 21 ].…”
Section: Discussionsupporting
confidence: 91%
“…Laparoscopic cholecystectomy is considered the gold standard for patients with symptoms or complications from gallstones. However, cholecystectomy in older people is associated with higher perioperative complications, prolonged hospital stay, and increased mortality compared to younger adults, which is explained by preexistent comorbidities and reduced physiologic reserve in this age group (van Heesewijk et al 2019;Loozen et al 2017). In patients with acute cholecystitis who are at very-high surgical risk and require an emergent intervention, percutaneous drainage with a cholecystostostomy tube has been the standard of care (Okamoto et al 2018).…”
Section: Gallstonesmentioning
confidence: 99%
“…Recently, some studies have reported poor surgical outcomes for LC in older patients [ 9 , 10 ]. Nevertheless, data on clinical characteristics of the disease and on the surgical outcomes of LC in elderly patients with AC are still lacking.…”
Section: Introductionmentioning
confidence: 99%